Strategy for Strengthening Madrasah Human Resource Governance in Facing the Challenges of Islamic Education Reform - Mawardi; Khairil Mufid; Darul Qotni; Mona Novita (Journal of Educational Management Research, 2026)
This study aims to identify strategies for strengthening madrasah human resource governance by integrating the development of pedagogical and managerial competencies to respond to the demands of Islamic education reform in the digital era. The study used a qualitative approach with a case study design at MAN 2 Sarolangun, using in-depth interviews, participant observation, and document analysis as data collection techniques. The results of the study indicate that managerial problems, structural barriers, teacher competency mismatches, and limitations in professional development programs interact with each other, resulting in HR management remaining administrative, reactive, and not fully adaptive to Islamic education reform. The theoretical implications of this study emphasize the need for a holistic model of madrasah HR governance, combining managerial, pedagogical, and Islamic value aspects, while the practical implications highlight the importance of developing competency-based professional programs and monitoring teacher needs to improve the quality of learning and the consistency of policy implementation. This study provides guidance for madrasah principals and policy makers in strengthening HR systematically.